Cultural and Organizational Influences on Employee Turnover Intentions in Vietnam's Independent Auditing Sector - Pham Huy, Hung (Commercium : Journal of Business and Management, 2025)
This study addresses the question of how cultural and organizational factors influence employees' turnover intentions in Vietnam's independent auditing sector. It was conducted to better understand the interaction between national culture and organizational practices in shaping auditors' decisions to stay or leave, with the ultimate goal of providing insights that could enhance employee retention strategies in Vietnamese auditing firms. Using qualitative research methods, including in-depth interviews and two focus group discussions with 18 auditors and  human resources managers from 15 Big 4 and non-Big 4 auditing firms, the study found that respect for hierarchical management structures, collectivist values, and indirect communication strongly influence how employees respond to managerial leadership, workload, and promotion opportunities. The findings demonstrate that cultural alignment with organizational values fosters loyalty, while misalignment drives auditors' turnover intentions in Vietnam's independent auditing firms. These results are significant as they highlight the limitations of applying human resource models from developed countries to Vietnam without adaptation and emphasize the need for culturally aligned management practices. The implications suggest that auditing firm leaders must design contextually appropriate strategies that balance organizational goals with Vietnam's cultural norms to minimize turnover and promote organizational stability.